Ali's well that ends well : tales of desperation and a little inspiration - Wentworth, Alexandra (Harper, an imprint of HarperCollins Publishers, 2022)
Like many, Ali Wentworth spent the pandemic seesawing between highs, lows, and baking an unnecessary amount of chocolate cake. Between binging every tv show in existence to conquering TikTok to becoming a (semi) empty-nester, Ali experienced her share of turmoil (including an early case of Covid), but she also grew a little, learned a lot, and found comfort in some unexpected people and places.